Sustainably Adjusting the Up-Conversion White-Emitting Luminescence Properties of GdAlO3: Er3+/Yb3+/Tm3+ Phosphors - Deng, Taoli; Jiang, Xianbang; Zhang, Qiuyun (Frontiers in Chemistry, 2020)
Doping heteroatom in phosphor can effectively improve luminescent properties, which has attracted great attention recently. GdAlO3 phosphors (GAP) doped with Er3+/Yb3+/Tm3+ were prepared via the co-precipitation method. Upon 980 nm excitation, strong blue, green, and red up-conversion (UC) emissions centered at 476, 524, 546, and 659 nm were observed, which could be successfully combined to form pure white light. It was found that changing the doping concentration of Er3+ and Yb3+ ions, the calcination temperature of the precursor, the laser power of the excitation light source, and doping Li+ could systematically adjust red/green/blue colors of GdAlO3:Er3+/Yb3+/Tm3+ phosphors to optimize the white emitting luminescence. When the Er3+ doping concentration of the phosphors increased, each color distribution successfully moved, making the maximum shift of the CIE coordinate. Finally, the influence of each factor on adjusting the UC white light performance and its mechanism were explored.